Movement Control Order (MCO): An Syar'iyyah Political Approach - Mohd Zulhazrin Mizan; Ahmad Aizuddin Hamzah; Kauthar Razali; Mohd Norazmi Nordin; Suddin Lada; Nor Adila Mohd Noor; Asrizam Esam (Spring, 2021)
Covid-19 is a pandemic that has been declared by the World Health Organization (WHO) as a pandemic that has claimed many lives around the world. As of January 1, 2021, the world has recorded at least two million infected victims. Implementing the movement control order is one of the best ways implemented by the government today in curbing the Covid-19 epidemic until a vaccine is available. The method of discussion found in this article is based on document analysis by referring to authoritative books, journals, articles, and websites. The study's findings found that the Movement Control Order implemented by the Malaysian government is based on 'Siyasah Syar'iyyah' in maintaining and curbing the spread of Covid19 in Malaysia.